2017
DOI: 10.1371/journal.pone.0187055
|View full text |Cite
|
Sign up to set email alerts
|

High temperature enhances the ability of Trichoderma asperellum to infect Pleurotus ostreatus mycelia

Abstract: Trichoderma asperellum is one of the species which can be isolated from contaminated Pleurotus ostreatus cultivation substrate with green mold disease. This study focused on the relationship between high temperature and infectivity of T. asperellum to P. ostreatus. Antagonism experiments between T. asperellum and P. ostreatus mycelia revealed that high temperature-treated P. ostreatus mycelia were more easily infected by T. asperellum and covered by conidia. Microscopic observation also showed that P. ostreatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…They can easily be attacked by the highly efficient phosphate solubilizing T. harzianum. Several studies [20,82] reported that high temperature could induce T. asperellum mycelia to form a massive number of conidia in a short time and speed up the spread of conidia, forming a sizeable infected area with Trichoderma.…”
Section: Rate and Speed Of Growthmentioning
confidence: 99%
“…They can easily be attacked by the highly efficient phosphate solubilizing T. harzianum. Several studies [20,82] reported that high temperature could induce T. asperellum mycelia to form a massive number of conidia in a short time and speed up the spread of conidia, forming a sizeable infected area with Trichoderma.…”
Section: Rate and Speed Of Growthmentioning
confidence: 99%
“…Thus, high temperature is the most adverse stress in the cultivation of P. ostreatus. After high-temperature stress, mycelial growth is inhibited, mycelia are susceptible to infection by pathogens, such as Trichoderma asperellum, and apoptotic-like cell death can occur (Song et al, 2014;Qiu et al, 2017). These adverse effects cause enormous economic losses, which urgently call for studies on the mechanism of P. ostreatus resistance to heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…High temperature not only inhibits mycelial growth and fruiting body formation, but also enhances Trichoderma sp. infection and cell membrane fluidity in edible fungi (Lu et al, 2014;Liu et al, 2017;Qiu et al, 2017). Previous studies have reported that Para-aminobenzoic acid (PABA) synthase and nitric oxide reduced ROS (reactive oxygen species) accumulation to alleviate oxidative damage induced by heat stress (Kong et al, 2012a;Lu et al, 2014); catalase, trehalose, HSP and calcium-calmodulin play an important role in regulating the response of the edible fungi to heat stress (Kong et al, 2012b;Deng et al, 2014;Wang et al, 2017;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%